2017
DOI: 10.1016/j.bbagen.2016.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Fructose suppresses uric acid excretion to the intestinal lumen as a result of the induction of oxidative stress by NADPH oxidase activation

Abstract: Single administration of fructose decreases in BCRP homodimer level, resulting in the suppression the function of ileal uric acid excretion. The suppression of the function of ileal uric acid excretion by single administration of fructose is caused by the activation of Nox. The results of our study provide a new insight into the mechanism of fructose-induced hyperuricemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 53 publications
1
24
0
3
Order By: Relevance
“…It has been reported that metabolism of fructose stimulates UA production, since transient ATP depletion commonly occurs with the generation of AMP [55] and reduced UA excretion [56]. Briefly, during fructose metabolism, fructose is phosphorylated into fructose 1-phosphate in a reaction catalyzed by fructokinase primarily in the liver.…”
Section: Fructose Metabolism and The Mechanisms By Which Fructose mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that metabolism of fructose stimulates UA production, since transient ATP depletion commonly occurs with the generation of AMP [55] and reduced UA excretion [56]. Briefly, during fructose metabolism, fructose is phosphorylated into fructose 1-phosphate in a reaction catalyzed by fructokinase primarily in the liver.…”
Section: Fructose Metabolism and The Mechanisms By Which Fructose mentioning
confidence: 99%
“…Moreover, long-term fructose administration suppresses renal excretion of UA, resulting in elevated serum UA levels [19]. Kaneko and colleagues found that a single administration of fructose affects the excretion of UA to the intestinal lumen, inducing the suppression of BCRP dimerization by reactive oxygen species (ROS)-derived production of dinucleotide phosphate (NADPH) oxidase (NOX) [56]. …”
Section: Fructose Metabolism and The Mechanisms By Which Fructose mentioning
confidence: 99%
See 1 more Smart Citation
“…The current study further found that high dose UA directly impaired NO generation in cultured human umbilical vein ECs, suggesting that hyperuricemia impairs vascular function by a mechanism of inhibition of NO production. In this regard, high dose may increase the activity of nicotinamide adenine dinucleotide phosphate oxidase that prompts oxidative stress and decreases the bioavailability of NO (22). Further, hyperuricemia impairs vascular function by increasing inflammation cytokine expression in IL-6, IL-8 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the reduction of intestinal excretion of UA [23,24] is an important cause of HUA. Intestinal UA excretion is regulated by urate transporters [25] , such as ABCG2, GLUT9, MRP4 and NPT5. Many studies have demonstrated that ABCG2 [26] is expressed in the gastrointestinal tract at high levels, especially in the intestine, which plays an important role in excreting UA from intestine into feces.…”
Section: Introductionmentioning
confidence: 99%